Connections and performance in bankers' turnover: better wed over the mixen than over the moor - Erich Battistin; Clara Graziano; Bruno Maria Parigi (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this paper we study top executive turnover in Italian Banks over the period 1993-2001. We relate the probability of survival of top executives (Presidents, CEOs and General Managers) to bank performance and the manager's local connections, controlling for (observable and unobservable) bank and manager characteristics by exploiting longitudinal information on bank-manager appointments. We measure the extent? of managers' local connections by the distance between the province of the bank's headquarters and the manager's province of birth. We show that top managers tend to be local in the sense that the distribution of this distance is heavily skewed towards zero. On the basis of this evidence, we address two questions. First, we investigate whether connections affect the duration of the appointment at the bank. Second, we ask whether connections entrench managers at the expense of the bank's performance. We find that connections generally increase the probabilities of managers surviving at their banks, and that the positive effect of performance on tenure (as amply documented by the executive turnover literature) disappears once connections are taken into account. On the other hand, we provide evidence against the hypothesis that managerial connections contain information valuable for enhancing a bank's performance. In particular, we find that highly connected boards cause the shorter survival of banks, and that those who benefit from connections are top managers themselves (mostly Presidents and General Managers). This suggests that connections may be collusion devices with which to maintain and share rents.
Keywords: J40; J63; G21; G34; 330; Connections; executive turnover; commercial and cooperative banks; Bankmanager; Arbeitsmobilität; Bank; Unternehmensentwicklung; Soziales Netzwerk; Kreditgenossenschaft; Italien